2021
DOI: 10.4103/ijd.ijd_651_20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Post-Kala-azar Dermal Leishmaniasis

Abstract: Post-kala-azar dermal leishmaniasis (PKDL) is a cutaneous sequel of visceral leishmaniasis (VL) or kala-azar and has become an entity of epidemiological significance by virtue of its ability to maintain the disease in circulation during inter-epidemic periods. PKDL has been identified as one of the epidemiological marker of “kala-azar elimination programme.” Data obtained in 2018 showed PKDL distribution primarily concentrated in 6 countries, which includes India, Sudan, south Sudan, Bangladesh, Ethiopia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…This study was an extension of a randomized sampling mode study where suspected cases of PKDL reported at a medical camp, and after confirmation of diagnosis were randomly allocated Miltefosine or LAmB depending on drug availability [ 13 ]. In 2010, the prevalence of PKDL was reported to range from 4.4 to 7.8 per 10,000 endemic population, and later declined to 1.1 per 10,000 population in a 2017 study [ 56 and references therein]. Accordingly, taking a real world, pragmatic approach, sample size calculation was not attempted.…”
Section: Discussionmentioning
confidence: 99%
“…This study was an extension of a randomized sampling mode study where suspected cases of PKDL reported at a medical camp, and after confirmation of diagnosis were randomly allocated Miltefosine or LAmB depending on drug availability [ 13 ]. In 2010, the prevalence of PKDL was reported to range from 4.4 to 7.8 per 10,000 endemic population, and later declined to 1.1 per 10,000 population in a 2017 study [ 56 and references therein]. Accordingly, taking a real world, pragmatic approach, sample size calculation was not attempted.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnoses and treatment of VL, CL, MCL, and PKDL are complicated by non-specific presentations early in the course of each disease [ 9 ]. Co-infection with HIV presents an important manifestation of leishmaniasis infection as its clinical presentation is often atypical and, therefore, further obscures accurate diagnosis in communities with high HIV prevalence [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCL and PKDL data is scarcer than VL and CL data in Kenya. It is estimated that PKDL occurs in less than 5% of VL cases in Kenya, although research on PKDL is not as common [ 9 ]. It is within this context that leishmaniasis research has been conducted in Kenya for the last 90 years.…”
Section: Introductionmentioning
confidence: 99%
“…Dewan et al [31] explored the spatial and temporal patterns of VL by studying hospital-onset VL cases in prevalent regions of Bangladesh. In diverse areas of India, Ghosh et al [32] researched the epidemiology of post-kala-azar cutaneous leishmaniasis and found that PKDL is mostly concentrated in the plains below 600 m above sea level, which is associated with sandfly habitat. There are also scholars who consider the fractional order of biological systems [33][34][35].…”
Section: Introductionmentioning
confidence: 99%